1996
DOI: 10.1002/jhet.5570330233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of azolylalkylquinolines with cytotoxic activity

Abstract: The syntheses of various azolylalkylquinoline derivatives in which the nature of the linkage between the quinoline and azolylalkyl moieties of the molecule were altered are described. The compounds were tested for cytotoxic activity towards cancer cells and compound 27 was found to exhibit moderate in vivo activity in a murine sarcoma model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…For medical and pharmaceutical applications of chiral tricyclic compounds, see: Abel et al (1996); Salvati et al (2005). For the synthesis of the starting reagent, 2-(p-tolyl)-3a,4,7,7a-tetrahydro-1H-4,7-methanoisoindole-1,3(2H)-dione, see: Andrade & Evilazio (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…For medical and pharmaceutical applications of chiral tricyclic compounds, see: Abel et al (1996); Salvati et al (2005). For the synthesis of the starting reagent, 2-(p-tolyl)-3a,4,7,7a-tetrahydro-1H-4,7-methanoisoindole-1,3(2H)-dione, see: Andrade & Evilazio (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…The derivatives of exo-5,6-dehydronorcantharidin are of great pharmacological interest and have attracted considerable attention (Abel et al, 1996;Deng et al, 2005). Furthermore, molecules of this type containing nitrogen have become a hot topic in heterocyclic chemistry because of their antitumour, antiviral, analgesic, sedative and fungicidal activities (Salvati et al, 2005).…”
Section: Commentmentioning
confidence: 99%
“…A series of azolylalkylquinilines have been previously reported as potent and selective cytotoxic agents in vitro 10. Recently, further research on this class of compounds reported that a series of novel cytotoxic azolylthioalkyl‐ureidoquinoline derivatives named SRA‐HX‐(1‐3) (Fig.…”
Section: Introductionmentioning
confidence: 99%